Analyzing Learner Needs for Developing Task-Based English Teaching Materials with Character Education Values for Young Learners - Inawati, Iin; Ikhsanudin, Ikhsanudin; Santosa, Hardi; Kustini, Siti (JOLLT Journal of Languages and Language Teaching, 2025)
This study investigates young learners’ needs in developing task-based English teaching materials that embed character education values. Although task-based language teaching (TBLT) has gained broad recognition, limited research in the Indonesian context has examined how character education values can be systematically integrated into TBLT materials for primary school students. To address this gap, a mixed-methods design was employed, combining quantitative data from student questionnaires with qualitative insights from teacher and principal interviews. This methodological triangulation ensured a more valid and comprehensive understanding of learners’ personal and instructional needs. Participants included 424 elementary students, three English teachers, and three principals from Muhammadiyah schools in Yogyakarta, Indonesia. The findings indicate that students’ personal needs are influenced by age, gender, cultural background, and attitudes toward English learning, while their learning needs reflect preferences in learning styles, teaching media, instructional techniques, thematic choices, language proficiency, and the inclusion of character-related content. The study provides empirically grounded insights to guide English curriculum design in Muhammadiyah schools, fostering the integration of moral and linguistic goals within task-based instruction, and offering a transferable framework for English language education in Indonesia and comparable contexts.